Application of structural model of glucose-insulin relations to assess beta-cell function and insulin sensitivity. - Turner, R; Rudenski, A; Matthews, DR; Levy, J; O'Rahilly, S; Hosker, J (1990)
A structural mathematical model of glucose-insulin relationships based on known quantitative responses of the major organs involved with glucose metabolism has been computed. Different degrees of beta-cell function and insulin sensitivity can be included, and the effect of their interaction assessed (i) in a steady state, basal homeostasis after an overnight fast and (ii) in response to a glucose infusion. By comparing a patient's basal plasma glucose and insulin (or C-peptide) concentrations with the predictions of a basal homeostatic model, the degree of impairment of beta-cell function and insulin sensitivity can be assessed. Similarly, the plasma glucose and insulin (or C-peptide) concentrations after a continuous glucose infusion can also be compared with predictions from the model to estimate beta-cell function and insulin sensitivity. These assessments of pathophysiology can be applied to data from individual patients or to patient populations.